The Influence of Death Awareness on Goal Achievement Reflected in Jenny Downham's Novel Before I Die (2007) - Fauziyah, Diyah, Dr. M. Thoyibi, M.S (2016)
This study is about The Influence of Death Awareness on Goal Achievement in Jenny Downham's Before I Die (2007) which is analyzed by using Individual Psychology approach. The objectives of the study are to know the indicators of the approaching death on a cancer sufferer, to know the response of a cancer sufferer to the approaching death, to know how death awareness influenced goal achievement on a cancer sufferer, and to reveal the reason why Jenny Downham addressed the medical case on Before I Die novel based on Individual Psychology approach. This research belongs to qualitative research. The primary data of this research is Before I Die by Jenny Downham in 2012, while the secondary data of this research are other sources related to the study, such as: website, dictionary and some books which support this research. The researcher draws three conclusions in this research. Firstly, the indicators of the approaching death on a cancer sufferer, physical changes, increased sleep and reduced appetite, changes of attitudes, and special request. Secondly, the response of a cancer sufferer to the approaching death includes being depressed, envy, accepting the reality, and making use the remaining time. Third is the influence of death awareness on goal achievement are people can appreciate their remaining time of life, having spirit to live, and having desire to do something strange which normal people do not. Fourth is the author wants to make clear that death is obvious.